What are you thinking? Acculturation as an activating event for negative evaluative beliefs among Latinos/as. Issue 3 (4th May 2019) - Archuleta, Adrian J.
ABSTRACT: Negative evaluative beliefs and other cognitive structures have been tied to psychological distress across various populations but have not been sufficiently incorporated into acculturation models. The current study examines the relationships between acculturation and various activating events and mediating sources of support related to negative evaluative beliefs among people of Mexican descent ( N = 319). Overall, model variables explained 26% of the variance in negative evaluative beliefs. Acculturation, marital commitment, and social capital associated with friends were negatively related to negative evaluative beliefs. Conversely, single relationship status, marital reward value, psychosocial stressors, and bridging social capital were positively related, and likely serve as activating events for negative evaluative beliefs. Identifying mechanisms related to psychological distress as well as supportive structures may help in constructing interventions that will address the specific needs of different groups. Future research should continue to explore appraisal and associated beliefs in acculturation models to understand why acculturative experiences may become stressful.